2021
DOI: 10.3390/ani11123601
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Dietary Microalgae Ameliorates Intestinal Parameters, Improves Body Weight, and Reduces Thawing Loss of Fillets in Broiler Chickens: A Pilot Study

Abstract: This pilot investigation aimed at studying the feasibility of using a low dose (0.2%) of dietary microalgae as a means of improving intestinal morphometry, body weight, and selected meat quality parameters in broilers. A total of 72 one-day-old ROSS 308 male chicks were randomly separated into four groups; three experimental pens in which the birds were fed with biomass from Tysochrysis lutea, Tetraselmis chuii, and Porphyridium cruentum over 30 days and a control group. T. chuii and P. cruentum had a positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
(100 reference statements)
0
8
0
Order By: Relevance
“…Intestinal epithelial cells are considered crucial constituents of the gut ecosystem as they not only partake in protection against invading pathogens but are also involved in nutrient acquisition [ 43 , 44 ]. Alternatives to improve intestinal architecture have been tested with success, including plant extracts, microalgae biomass, or probiotics [ 24 , 45 , 46 ]. Salmonella serovars, including S .…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal epithelial cells are considered crucial constituents of the gut ecosystem as they not only partake in protection against invading pathogens but are also involved in nutrient acquisition [ 43 , 44 ]. Alternatives to improve intestinal architecture have been tested with success, including plant extracts, microalgae biomass, or probiotics [ 24 , 45 , 46 ]. Salmonella serovars, including S .…”
Section: Discussionmentioning
confidence: 99%
“…Although it was not studied in combination with phytogenics, increasing number of investigations have shown that dietary administration of algae alone improved also growth performances in poultry ( 2 , 25 , 56–58 ). Here, it is clear that the encapsulated phytogenic-phycogenic combination synergistically improved growth performance in broilers, and therefore its underlying mechanism warrants further in-depth investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement of villi height results in the better absorption of nutrients, and as a result, the study found a significant improvement in BW gain. A study on broiler chickens with different microalgae species ( Tysochrysis lutea, Tetraselmis chuii, Porphyridium cruentum ) also reported the improvement of gut morphology, especially of duodenum and ileum ( Šefcová et al, 2021 ). The potential reason for the improvement in gut morphology in the study might be due to the presence of oligosaccharides in A. platensis .…”
Section: Discussionmentioning
confidence: 99%